Innamincka Words: Yandruwandha dictionary and stories - Breen, Gavan (ANU Press, 2015)
Innamincka Words: Yandruwandha dictionary and stories is one of a pair of companion volumes on Yandruwandha, a dialect of the language formerly spoken on the Cooper and Strzelecki Creeks and the country to the north of the Cooper, in the northeast corner of South Australia and a neighbouring strip of Queensland. The other volume is entitled Innamincka Talk: a grammar of the Innamincka dialect of Yandruwandha with notes on other dialects. Innamincka Words is for readers, especially descendants of the original people of the area, who are interested in the language. It is also a necessary resource for users of the more technical Innamincka Talk. These volumes document all that could be learnt from the last speakers of the language in the last years of their lives by a linguist who was involved with other languages at the same time. These were people who did not have a full knowledge of the culture of their forebears, but were highly competent, indeed brilliant, in the way they could teach what they knew to the linguist student.